Final answer:
The general rule for the sequence is an = -9 + (n-1)(9). The first term (a1) is -9 and the common difference is 9.
Step-by-step explanation:
Sequence Analysis:
To find the general rule for a sequence, we need to determine the pattern or relationship between the terms. In this case, we are given a4 = 18 and a7 = 9. To find the common difference, we subtract the two terms: 18 - 9 = 9. So, the common difference is 9. To find a1, we can use the formula: an = a1 + (n-1)d, where n is the term number and d is the common difference. Substituting n = 4, a4 = 18, and d = 9, we can solve for a1. 18 = a1 + (4-1)(9), which gives us a1 = 18 - 3(9) = 18 - 27 = -9. Therefore, the general rule for this sequence is an = -9 + (n-1)(9). The first term (a1) is -9 and the common difference is 9.